Impact of transcranial magnetic stimulation therapy on the volumes of amygdala and hippocampal subfields in patients with major depressive disorder - WANG Sirui; KONG Gai; LI Hui; QIAN Zhenying; CUI Huiru; TANG Yingying (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To investigate the longitudinal changes in amygdala and hippocampal subfield volumes before and after transcranial magnetic stimulation (TMS) treatment in patients with major depressive disorder (MDD) and explore their correlation with the antidepressant and anxiolytic efficacy of TMS.Methods·A total of 58 patients diagnosed with MDD at Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, were included in this study between January 2018 and August 2023. Clinical depressive and anxiety symptoms were assessed by using the Hamilton Depression Scale (HAMD), Montgomery-Asberg Depression Rating Scale (MADRS), and Hamilton Anxiety Scale (HAMA) at baseline and post-TMS treatment. Patients underwent a baseline magnetic resonance imaging (MRI) scan followed by TMS treatment targeting the left dorsolateral prefrontal cortex (DLPFC) at a frequency of 10 Hz, totaling 20 sessions. A follow-up MRI scan was conducted on the same day the TMS treatment concluded. Amygdala and hippocampal subfield volumes were segmented and calculated by using FreeSurfer v6.0.0 software. Longitudinal changes in the subfield volumes were analyzed with two-way analysis of variance. Controlling for age, sex, and intracranial volume, partial correlation analysis was conducted between subfield volumes and baseline clinical scores. The association between the rate of volume change in brain regions with significant volume changes and symptom improvement (reduction in HAMD, MADRS, and HAMA scores) was evaluated.Results·Following TMS treatment, a significant increase in the volume of the right amygdala central nucleus was observed (t=-2.441, P=0.018). While the volumes of bilateral hippocampal fimbria decreased, the volumes of most hippocampal subfield and the total hippocampus increased (P<0.05). No significant correlations were found between baseline amygdala or hippocampal subfield volumes and clinical depressive and anxiety symptoms. However, only in patients who responded effectively to TMS treatment, a positive correlation was found between the volume change rate of the left hippocampal tail and reductions in anxiety symptoms (HAMA: r=0.334, P=0.044).Conclusion·High-frequency TMS targeting the left DLPFC may induce volume increases in the right amygdala central nucleus and specific hippocampal subfields. Additionally, the volume change rate of the left hippocampal tail is associated with anti-anxiety effects in TMS responders, suggesting that high-frequency TMS targeting the left DLPFC may induce neuroplastic changes in the central nucleus of the right amygdala and key subfields of the hippocampus.